PENGARUH ETOS KERJA DAN KOMUNIKASI TERHADAP PRESTASI KERJA PEGAWAI DI DINAS LINGKUNGAN HIDUP KABUPATEN NIAS SELATAN - Lisnidar Laia (Jurnal Ilmiah Mahasiswa Nias Selatan, 2022)
The purpose of 0this study was to determine the influence of work ethic and communication on the work performance of employees in the Environment Agency of South Nias Regency. The type of research used is a causal quantitative type. The source of the data was employees, with the population and sample in this study being 35 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is multiple regression analysis. The results of this study showed that the Fhitung value of 59,660>Ftabel was 3,295. This research can be concluded that there is an influence of work ethic and communication on the work performance of employees in the Environment Agency of South Nias Regency. The suggestions for this research are (1) To improve work performance, it is necessary to provide a work ethic through facilities to facilitate organizational activities. (2) Organizations should place more emphasis on their employees to better understand communication from superiors and subordinates, if there is something less clear and difficult to understand